Murine malaria: resistance of AXB/BXA recombinant inbred mice to Plasmodium chabaudi. - Stevenson, M M (1985)
The level of resistance to infection with Plasmodium chabaudi is genetically controlled. We have previously reported that a single dominant gene is responsible for the variation in host resistance to malaria between susceptible A/J- and resistant C57BL-derived mice. In the present study, recombinant inbred strain analysis was performed with AXB/BXA recombinant inbred strains derived from A/J and C57BL/6 progenitors. Typing of 17 AXB/BXA recombinant inbred strains confirmed the unigenic control of inheritance in this particular strain combination and allowed us to demonstrate genetic linkage between the traits of resistance (defined as a prolonged survival and a low peak parasitemia) and the magnitude of splenomegaly. The influence of sex on the course of infection, which we previously reported in the examination of segregating populations (Stevenson et al., Infect. Immun. 38:80-88, 1982), was again demonstrated in the survey of RI strains.